2020
DOI: 10.1371/journal.pone.0240257
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis, genetic diversity and drug sensitivity patterns of Mycobacterium tuberculosis strains isolated from tuberculous meningitis patients at a tertiary care hospital in South India

Abstract: Tuberculous meningitis (TBM) is the most severe form of Mycobacterium tuberculosis (Mtb) infection in humans and is a public health concern worldwide. We evaluated the performance of GeneXpert MTB/RIF (GeneXpert) for the diagnosis of TBM. In addition, genetic diversity and drug susceptibility profiling of Mtb strains isolated from TBM patients were also investigated. A total of 293 TBM suspected cerebrospinal fluid (CSF) samples were collected and subjected to GeneXpert and Mycobacterial Growth Indicator Tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this regard, the findings observed in this study seem to agree with others that suggested a possible relationship between L3 and EPTB disease [ 12 , 38 ] . Correspondingly, a significantly higher rate of PTB was often associated with L4, while more EPTB disease, such as TB meningitis and TBLN, was attributed to L3 [ 13 , 15 , 38 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the findings observed in this study seem to agree with others that suggested a possible relationship between L3 and EPTB disease [ 12 , 38 ] . Correspondingly, a significantly higher rate of PTB was often associated with L4, while more EPTB disease, such as TB meningitis and TBLN, was attributed to L3 [ 13 , 15 , 38 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Although, it is still challenging to investigate the influence of bacterial and host genotype on the development of different forms of TB in humans, disease phenotype seems to be associated with a bacterial genotype [2,6]. According to other published reports, L4 seemed more likely to be associated with Pulmonary TB (PTB) while L2 and L3 were linked with extra-pulmonary TB (EPTB) disease, such as TB meningitis and TB in cervical Lymph Nodes (TBLN) [12][13][14][15]. Another comparative study showed that strains of the East African Indian (L3) and Euro-American (L4) lineages were negatively associated with extra thoracic disease as compared to strains of the East Asian lineage (L2) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the pharmacogenomics of infectious diseases (e.g., AIDS, tuberculosis, malaria, and COVID-19) is important for African populations, while the pharmacogenomics of cardiovascular diseases is becoming important, as is the case for cancer and hypertension. Several studies have shown resistance due to genetic variations in two of the most expanded infectious diseases in Africa, AIDS (91) and tuberculosis (34,58,107).…”
Section: Percentage Of Populationmentioning
confidence: 99%